Flexible Low Temperature Solution Processed Oxide Semiconductor TFT Backplanes for Use in AMOLED Displays. Issue 1 (June 2014) - Cobb, Brian; Rodriguez, Francisco Gonzalez; Maas, Joris; Ellis, Tim; van der Steen, Jan‐Laurens; Myny, Kris; Smout, Steve; Vicca, Peter; Bhoolokam, Ajay; Rockelé, Maarten; Steudel, Soeren; Heremans, Paul; et al.
Abstract AMOLED backplanes were fabricated on both rigid glass and flexible plastic substrates using a solution processed oxide semiconductor processed at temperatures <250C with mobilities greater than 2 cm2/Vs. The backplanes were integrated onto a thin film moisture barrier and QQVGA AMOLED displays were successfully fabricated.